THE PROPHET YAHYA ( Peace Of Allah Be Upon him) In SABIANS CHRISTIANITY and ISLAM - A Contrastive Study - Humadi, Thabit (Islamic Sciences Journal, 2023)
Sabians, Christianity and IsLam agree unanimously on prophecy or sacredness of the prophet John ( peace of Allah be up on him) and he was born to a old father and a barren mother. They agreed also on the fact that the Divine Entity did a miracle and responded to a true prayer by the prophet John to have a boy not became of paternity but to keep the prophetic heritage and God,s guidance, and Allah did.